PELAKSANAA PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI HIMPUNAN - Dian Kusmaharti (Jurnal Pendidikan Dasar, 2019)
Abstract: This research is aim to know effectivity implementation of problem based learning. Effectivity of problem based learning applied on related set material with the relation of two sets and set operations. This research use qualitative research with research subjects the student of 2019-A PGRI Adi Buana Surabaya. The source of the data that used in this study come from students who followed the study with data collection techniques through by test consist of writing test and non test. Non test data obtained by researchers through: observation, interview, questionnaire, and documentation during implementation of problem based learning. Researcher use triangulation method as validity and data analysis which is obtained. The result of this research illustrate implementation of problem based learning can be done well for set material on the students of PGSD UNIPA Surabaya 2019-A. This matter know from learning target achievement that implementation of syntax on problem based learning as much 87,15% students have good attitude competencies during problem based learning. And also punctuality in implementation of problem based learning according to the specified learning time allocation on research contract before the process implementation problem based learning bagins. Beside that, acquisition of the effectiveness of the achievement activity the students learning give possitive effect as much 77,89% students have high learning activity, and students have get above average value as much 83,32%. Keyword : problem based learning, set, learning process, learning achievement.